The acoustic detection of the Franciscana dolphin ( Pontoporia blainvillei ), in open sea off the coast of Argentina - G. Giardino; P. Denuncio; E. Papale; M. Ceraulo; G. Buscaino; R. Bastida; D. Rodríguez (New Zealand Journal of Marine and Freshwater Research, 2025)
The Franciscana dolphin ( Pontoporia blainvillei ) is facing significant threats in the Southwestern Atlantic Ocean, largely due to entanglement in artisanal fishing nets, which makes it the most threatened dolphin species in the region Its conservation calls for a standardised methodology that enables the detection and monitoring of dolphin populations on a longer temporal scale. This study represents the first acoustic monitoring of wild Franciscana dolphins in Argentina, focusing on understanding their diel patterns of activity and their relationship with environmental variables. Our findings show that Franciscana dolphin acoustic presence in summer in Chapadmalal (Argentina) is more frequent in January than in February and March and is influenced by the interaction between tide and wind direction. Specifically, at higher tide levels, wind direction has a reduced impact on dolphin detections. This interaction varies seasonally, with shifts observed in February and March. This research advances standardised methodologies for detecting and monitoring Franciscana dolphin populations, supporting efforts to improve their conservation.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Modeling the Underwater Sound of Floating Offshore Windfarms in the Central Mediterranean Sea - Marzia Baldachini; Robin D. J. Burns; Giuseppa Buscaino; Elena Papale; Roberto Racca; Michael A. Wood; Federica Pace (Journal of Marine Science and Engineering, 2024)
In the shift toward sustainable energy production, offshore wind power has experienced notable expansion. Several projects to install floating offshore wind farms in European waters, ranging from a few to hundreds of turbines, are currently in the planning stage. The underwater operational sound generated by these floating turbines has the potential to affect marine ecosystems, although the extent of this impact remains underexplored. This study models the sound radiated by three planned floating wind farms in the Strait of Sicily (Italy), an area of significant interest for such developments. These wind farms vary in size (from 250 MW to 2800 MW) and environmental characteristics, including bathymetry and seabed substrates. Propagation losses were modeled in one-third-octave bands using JASCO Applied Sciences’ Marine Operations Noise Model, which is based on the parabolic equation method, combined with the BELLHOP beam-tracing model. Two sound speed profiles, corresponding to winter and summer, were applied to simulate seasonal variations in sound propagation. Additionally, sound from an offshore supply ship was incorporated with one of these wind farms to simulate maintenance operations. Results indicate that sound from operating wind farms could reach a broadband sound pressure level (Lp) of 100 dB re 1 µPa as far as 67 km from the wind farm. Nevertheless, this sound level is generally lower than the ambient sound in areas with intense shipping traffic. The findings are discussed in relation to local background sound levels and current guidelines and regulations. The implications for environmental management include the need for comprehensive monitoring and mitigation strategies to protect marine ecosystems from potential acoustic disturbances.

Soundscape of a Mediterranean seashore during loggerhead sea turtle (Caretta caretta) spawning season - G. Buscaino; M. Arculeo; I. Cambera; A. Citarrella; D. D'Emanuele; M. Pelagatti; G. Sannino; A. Carillo; E. Papale (Marine Pollution Bulletin, 2023)

Drought Influences the Accuracy of Simulated Ecosystem Fluxes: A Model-Data Meta-analysis for Mediterranean Oak Woodlands - Rodrigo Vargas; Oliver Sonnentag; Gab Abramowitz; Arnaud Carrara; Jing Ming Chen; Philippe Ciais; Alexandra Correia; Trevor F. Keenan; Hideki Kobayashi; Jean-Marc Ourcival; Dario Papale; David Pearson; et al. (Ecosystems, 2013)

Effects of an epilepsy-causing mutation in the SCN1A sodium channel gene on cocaine-induced seizure susceptibility in mice - Ryan H. Purcell; Ligia A. Papale; Christopher D. Makinson; Nikki T. Sawyer; Jason P. Schroeder; Andrew Escayg; David Weinshenker (Psychopharmacology, 2013)

Fertile forests produce biomass more efficiently - S. Vicca; S. Luyssaert; J. Peñuelas; M. Campioli; F. S. Chapin; P. Ciais; A. Heinemeyer; P. Högberg; W. L. Kutsch; B. E. Law; Y. Malhi; D. Papale; et al. (Ecology Letters, 2012)
Ecology Letters (2012) Abstract Trees with sufficient nutrition are known to allocate carbon preferentially to aboveground plant parts. Our global study of 49 forests revealed an even more fundamental carbon allocation response to nutrient availability: forests with high‐nutrient availability use 58 ± 3% (mean ± SE; 17 forests) of their photosynthates for plant biomass production (BP), while forests with low‐nutrient availability only convert 42 ± 2% (mean ± SE; 19 forests) of annual photosynthates to biomass. This nutrient effect largely overshadows previously observed differences in carbon allocation patterns among climate zones, forest types and age classes. If forests with low‐nutrient availability use 16 ± 4% less of their photosynthates for plant growth, what are these used for? Current knowledge suggests that lower BP per unit photosynthesis in forests with low‐ versus forests with high‐nutrient availability reflects not merely an increase in plant respiration, but likely results from reduced carbon allocation to unaccounted components of net primary production, particularly root symbionts.

Identification of vegetation and soil carbon pools out of equilibrium in a process model via eddy covariance and biometric constraints - NUNO CARVALHAIS; MARKUS REICHSTEIN; PHILIPPE CIAIS; G. JAMES COLLATZ; MIGUEL D. MAHECHA; LEONARDO MONTAGNANI; DARIO PAPALE; SERGE RAMBAL; JÚLIA SEIXAS (Global Change Biology, 2010)
Assumptions of steady‐state conditions in biogeochemical modelling are often invoked because knowledge on the development status of the modelling domain is generally unavailable. Here, we investigate the role of vegetation pool sizes on nonequilibrium conditions through model‐data integration approaches for a set of sites using eddy covariance CO 2 flux data. The study is based on the Carnegie–Ames–Stanford Approach (CASA) model, modified (CASA G ) in order to evaluate the sensitivity of simulated net ecosystem production (NEP) fluxes to vegetation pool sizes. The experimental design is based on the inverse model optimization of different parameter vectors performed at the measurement site level. Each parameter vector prescribes different simulation dynamics that embody different model structural assumptions concerning (non)steady‐state conditions in vegetation and soil carbon pools. We further explore the potential of assimilating biometric constraints through the cost function for sites where in situ information on aboveground biomass or wood pools is available. The integration of biometric data yields marked improvements in the simulation of vegetation C pools compared to single constraints with eddy flux data. Overall, it is necessary to relax both vegetation and soil carbon pools for consistency with the observed data streams. Multiple constraints approaches also leads to variable model performance among the different experimental setups and model structures. We identify and assess the limitations of various model structures and the role of multiple constraints approaches for tackling issues of equifinality. These studies emphasize the need for establishing consistent data sets of fluxes and biometric data for successful model‐data fusion.

The European carbon balance. Part 3: forests - S. LUYSSAERT; P. CIAIS; S. L. PIAO; E.‐D. SCHULZE; M. JUNG; S. ZAEHLE; M. J. SCHELHAAS; M. REICHSTEIN; G. CHURKINA; D. PAPALE; G. ABRIL; C. BEER; et al. (Global Change Biology, 2010)
We present a new synthesis, based on a suite of complementary approaches, of the primary production and carbon sink in forests of the 25 member states of the European Union (EU‐25) during 1990–2005. Upscaled terrestrial observations and model‐based approaches agree within 25% on the mean net primary production (NPP) of forests, i.e. 520±75 g C m −2 yr −1 over a forest area of 1.32 × 10 6 km 2 to 1.55 × 10 6 km 2 (EU‐25). New estimates of the mean long‐term carbon forest sink (net biome production, NBP) of EU‐25 forests amounts 75±20 g C m −2 yr −1 . The ratio of NBP to NPP is 0.15±0.05. Estimates of the fate of the carbon inputs via NPP in wood harvests, forest fires, losses to lakes and rivers and heterotrophic respiration remain uncertain, which explains the considerable uncertainty of NBP. Inventory‐based assessments and assumptions suggest that 29±15% of the NBP (i.e., 22 g C m −2 yr −1 ) is sequestered in the forest soil, but large uncertainty remains concerning the drivers and future of the soil organic carbon. The remaining 71±15% of the NBP (i.e., 53 g C m −2 yr −1 ) is realized as woody biomass increments. In the EU‐25, the relatively large forest NBP is thought to be the result of a sustained difference between NPP, which increased during the past decades, and carbon losses primarily by harvest and heterotrophic respiration, which increased less over the same period.

Patterns and controls of the variability of radiation use efficiency and primary productivity across terrestrial ecosystems - Martín F. Garbulsky; Josep Peñuelas; Dario Papale; Jonas Ardö; Michael L. Goulden; Gerard Kiely; Andrew D. Richardson; Eyal Rotenberg; Elmar M. Veenendaal; Iolanda Filella (Global Ecology and Biogeography, 2010)
Aim The controls of gross radiation use efficiency (RUE), the ratio between gross primary productivity (GPP) and the radiation intercepted by terrestrial vegetation, and its spatial and temporal variation are not yet fully understood. Our objectives were to analyse and synthesize the spatial variability of GPP and the spatial and temporal variability of RUE and its climatic controls for a wide range of vegetation types. Location A global range of sites from tundra to rain forest. Methods We analysed a global dataset on photosynthetic uptake and climatic variables from 35 eddy covariance (EC) flux sites spanning between 100 and 2200 mm mean annual rainfall and between −13 and 26°C mean annual temperature. RUE was calculated from the data provided by EC flux sites and remote sensing (MODIS). Results Rainfall and actual evapotranspiration (AET) positively influenced the spatial variation of annual GPP, whereas temperature only influenced the GPP of forests. Annual and maximum RUE were also positively controlled primarily by annual rainfall. The main control parameters of the growth season variation of gross RUE varied for each ecosystem type. Overall, the ratio between actual and potential evapotranspiration and a surrogate for the energy balance explained a greater proportion of the seasonal variation of RUE than the vapour pressure deficit (VPD), AET and precipitation. Temperature was important for determining the intra‐annual variability of the RUE at the coldest energy‐limited sites. Main conclusions Our analysis supports the idea that the annual functioning of vegetation that is adapted to its local environment is more constrained by water availability than by temperature. The spatial variability of annual and maximum RUE can be largely explained by annual precipitation, more than by vegetation type. The intra‐annual variation of RUE was mainly linked to the energy balance and water availability along the climatic gradient. Furthermore, we showed that intra‐annual variation of gross RUE is only weakly influenced by VPD and temperature, contrary to what is frequently assumed. Our results provide a better understanding of the spatial and temporal controls of the RUE and thus could lead to a better estimation of ecosystem carbon fixation and better modelling.

Separation of net ecosystem exchange into assimilation and respiration using a light response curve approach: critical issues and global evaluation - GITTA LASSLOP; MARKUS REICHSTEIN; DARIO PAPALE; ANDREW D. RICHARDSON; ALMUT ARNETH; ALAN BARR; PAUL STOY; GEORG WOHLFAHRT (Global Change Biology, 2010)
The measured net ecosystem exchange (NEE) of CO 2 between the ecosystem and the atmosphere reflects the balance between gross CO 2 assimilation [gross primary production (GPP)] and ecosystem respiration (R eco ). For understanding the mechanistic responses of ecosystem processes to environmental change it is important to separate these two flux components. Two approaches are conventionally used: (1) respiration measurements made at night are extrapolated to the daytime or (2) light–response curves are fit to daytime NEE measurements and respiration is estimated from the intercept of the ordinate, which avoids the use of potentially problematic nighttime data. We demonstrate that this approach is subject to biases if the effect of vapor pressure deficit (VPD) modifying the light response is not included. We introduce an algorithm for NEE partitioning that uses a hyperbolic light response curve fit to daytime NEE, modified to account for the temperature sensitivity of respiration and the VPD limitation of photosynthesis. Including the VPD dependency strongly improved the model's ability to reproduce the asymmetric diurnal cycle during periods with high VPD, and enhances the reliability of R eco estimates given that the reduction of GPP by VPD may be otherwise incorrectly attributed to higher R eco . Results from this improved algorithm are compared against estimates based on the conventional nighttime approach. The comparison demonstrates that the uncertainty arising from systematic errors dominates the overall uncertainty of annual sums (median absolute deviation of GPP: 47 g C m −2 yr −1 ), while errors arising from the random error (median absolute deviation: ∼2 g C m −2 yr −1 ) are negligible. Despite site‐specific differences between the methods, overall patterns remain robust, adding confidence to statistical studies based on the FLUXNET database. In particular, we show that the strong correlation between GPP and R eco is not spurious but holds true when quasi‐independent, i.e. daytime and nighttime based estimates are compared.

Lava flow hazard at Nyiragongo volcano, D.R.C. - Massimiliano Favalli; Giuseppe D. Chirico; Paolo Papale; Maria Teresa Pareschi; Enzo Boschi (Bulletin of Volcanology, 2009)

Lava flow hazard at Nyiragongo Volcano, DRC - Giuseppe D. Chirico; Massimiliano Favalli; Paolo Papale; Enzo Boschi; Maria Teresa Pareschi; Arthur Mamou-Mani (Bulletin of Volcanology, 2009)

CO 2 balance of boreal, temperate, and tropical forests derived from a global database - S. LUYSSAERT; I. INGLIMA; M. JUNG; A. D. RICHARDSON; M. REICHSTEIN; D. PAPALE; S. L. PIAO; E. ‐D. SCHULZE; L. WINGATE; G. MATTEUCCI; L. ARAGAO; M. AUBINET; et al. (Global Change Biology, 2007)
Terrestrial ecosystems sequester 2.1 Pg of atmospheric carbon annually. A large amount of the terrestrial sink is realized by forests. However, considerable uncertainties remain regarding the fate of this carbon over both short and long timescales. Relevant data to address these uncertainties are being collected at many sites around the world, but syntheses of these data are still sparse. To facilitate future synthesis activities, we have assembled a comprehensive global database for forest ecosystems, which includes carbon budget variables (fluxes and stocks), ecosystem traits (e.g. leaf area index, age), as well as ancillary site information such as management regime, climate, and soil characteristics. This publicly available database can be used to quantify global, regional or biome‐specific carbon budgets; to re‐examine established relationships; to test emerging hypotheses about ecosystem functioning [e.g. a constant net ecosystem production (NEP) to gross primary production (GPP) ratio]; and as benchmarks for model evaluations. In this paper, we present the first analysis of this database. We discuss the climatic influences on GPP, net primary production (NPP) and NEP and present the CO 2 balances for boreal, temperate, and tropical forest biomes based on micrometeorological, ecophysiological, and biometric flux and inventory estimates. Globally, GPP of forests benefited from higher temperatures and precipitation whereas NPP saturated above either a threshold of 1500 mm precipitation or a mean annual temperature of 10 °C. The global pattern in NEP was insensitive to climate and is hypothesized to be mainly determined by nonclimatic conditions such as successional stage, management, site history, and site disturbance. In all biomes, closing the CO 2 balance required the introduction of substantial biome‐specific closure terms. Nonclosure was taken as an indication that respiratory processes, advection, and non‐CO 2 carbon fluxes are not presently being adequately accounted for.

Photosynthesis drives anomalies in net carbon‐exchange of pine forests at different latitudes - S. LUYSSAERT; I. A. JANSSENS; M. SULKAVA; D. PAPALE; A. J. DOLMAN; M. REICHSTEIN; J. HOLLMÉN; J. G. MARTIN; T. SUNI; T. VESALA; D. LOUSTAU; B. E. LAW; et al. (Global Change Biology, 2007)
The growth rate of atmospheric CO 2 exhibits large temporal variation that is largely determined by year‐to‐year fluctuations in land–atmosphere CO 2 fluxes. This land–atmosphere CO 2 ‐flux is driven by large‐scale biomass burning and variation in net ecosystem exchange (NEE). Between‐ and within years, NEE varies due to fluctuations in climate. Studies on climatic influences on inter‐ and intra‐annual variability in gross photosynthesis (GPP) and net carbon uptake in terrestrial ecosystems have shown conflicting results. These conflicts are in part related to differences in methodology and in part to the limited duration of some studies. Here, we introduce an observation‐driven methodology that provides insight into the dependence of anomalies in CO 2 fluxes on climatic conditions. The methodology was applied on fluxes from a boreal and two temperate pine forests. Annual anomalies in NEE were dominated by anomalies in GPP, which in turn were correlated with incident radiation and vapor pressure deficit (VPD). At all three sites positive anomalies in NEE (a reduced uptake or a stronger source than the daily sites specific long‐term average) were observed on summer days characterized by low incident radiation, low VPD and high precipitation. Negative anomalies in NEE occurred mainly on summer days characterized by blue skies and mild temperatures. Our study clearly highlighted the need to use weather patterns rather than single climatic variables to understand anomalous CO 2 fluxes. Temperature generally showed little direct effect on anomalies in NEE but became important when the mean daily air temperature exceeded 23 °C. On such days GPP decreased likely because VPD exceeded 2.0 kPa, inhibiting photosynthetic uptake. However, while GPP decreased, the high temperature stimulated respiration, resulting in positive anomalies in NEE. Climatic extremes in summer were more frequent and severe in the South than in the North, and had larger effects in the South because the criteria to inhibit photosynthesis are more often met.

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Reduction of ecosystem productivity and respiration during the European summer 2003 climate anomaly: a joint flux tower, remote sensing and modelling analysis - M. REICHSTEIN; P. CIAIS; D. PAPALE; R. VALENTINI; S. RUNNING; N. VIOVY; W. CRAMER; A. GRANIER; J. OGÉE; V. ALLARD; M. AUBINET; Chr. BERNHOFER; et al. (Global Change Biology, 2007)
The European CARBOEUROPE/FLUXNET monitoring sites, spatial remote sensing observations via the EOS‐MODIS sensor and ecosystem modelling provide independent and complementary views on the effect of the 2003 heatwave on the European biosphere's productivity and carbon balance. In our analysis, these data streams consistently demonstrate a strong negative anomaly of the primary productivity during the summer of 2003. FLUXNET eddy‐covariance data indicate that the drop in productivity was not primarily caused by high temperatures (‘heat stress’) but rather by limitation of water (drought stress) and that, contrary to the classical expectation about a heat wave, not only gross primary productivity but also ecosystem respiration declined by up to more than to 80 gC m −2 month −1 . Anomalies of carbon and water fluxes were strongly correlated. While there are large between‐site differences in water‐use efficiency (WUE, 1–6 kg C kg −1 H 2 O) here defined as gross carbon uptake divided by evapotranspiration (WUE=GPP/ET), the year‐to‐year changes in WUE were small ( −1 ) and quite similar for most sites (i.e. WUE decreased during the year of the heatwave). Remote sensing data from MODIS and AVHRR both indicate a strong negative anomaly of the fraction of absorbed photosynthetically active radiation in summer 2003, at more than five standard deviations of the previous years. The spatial differentiation of this anomaly follows climatic and land‐use patterns: Largest anomalies occur in the centre of the meteorological anomaly (central Western Europe) and in areas dominated by crops or grassland. A preliminary model intercomparison along a gradient from data‐oriented models to process‐oriented models indicates that all approaches are similarly describing the spatial pattern of ecosystem sensitivity to the climatic 2003 event with major exceptions in the Alps and parts of Eastern Europe, but differed with respect to their interannual variability.